Diagnosis of human herpesvirus 6B primary infection by polymerase chain reaction in young children with exanthematic disease - Ivna de Melo Magalhães; Rebeca Vasquez Novo Martins; Renata Oliveira Vianna; Solange Artimos Oliveira; Silvia Maria Baeta Cavalcanti (Revista da Sociedade Brasileira de Medicina Tropical, 2011)
INTRODUCTION: Exanthem subitum is a classical rash disease of early childhood caused by human herpesvirus 6B (HHV-6B). However, the rash is frequently misdiagnosed as that of either measles or rubella. METHODS: In this study, a nested multiplex polymerase chain reaction (PCR) was used to diagnose HHV-6B primary infection, differentiate it from infections caused by HHV-6A and compare it to antibody avidity tests. The samples were separated into case group and control group according to the results of the indirect immunofluorescence assay (IFA) technique. RESULTS: From the saliva samples analyzed, HHV-6A DNA was detected in 3.2% of the case group and in 2.6% of the control group. Regarding HHV-6B, PCR detected viral DNA in 4.8% of the case group and in 1.3% of the control group. Among the serum samples studied, a frequency of 1.7% was determined for HHV-6A in the case group and 1.2% in the control group. PCR did not detect HHV-6B DNA in serum samples. The sensitivity and specificity of the PCR technique ranged from 0% to 4.8% and 97.5% to 100%, respectively, compared to IFA. CONCLUSIONS: The PCR technique was not suitable for diagnosing primary infection by HHV-6B in children with exanthematic disease and should not substitute the IFA.